MSCs and innovative biomaterials in dentistry - Tatullo, Marco (Stem cell biology and regenerative medicine., 2017)
This authoritative reference presents the modern concepts of mesenchymal stem cells (MSCs) and biomaterials as they pertain to the dental field. The book is organized around three main topics: MSCs biology, advanced biomaterials, and clinical applications. The chapters present basic information on stem cell biology and physiology, modern biomaterials that improve bone tissue regeneration, the biomatrices like platelet-rich fibrin (PRF) used to functionalize the biomaterials surface, the strategic and safe intraoral seats of harvesting, the new sources for MSCs, as well as the future perspectives and new challenges in these exciting fields. The contributors are top scientists with a great deal of experience in regenerative dentistry and biomedical research. They offer an international perspective and are richly cross-disciplinary, representing academia, research, and industry. MSCs and Innovative Biomaterials in Dentistry is indispensable reading for students, researchers, and clinicians who need to stay up-to-date on the cutting-edge developments of tissue engineering and regenerative medicine applied to dental sciences.